Frey syndrome: factors influencing the time to event. Issue 7 (July 2015) - Lafont, M.; Whyte, A.; Whyte, J.; Saura, E.; Tejedor, M.T.
Abstract Frey syndrome is a common complication after parotidectomy. The time from surgery to disease onset may be quite long; therefore, a time-to-event analysis was performed for the occurrence of this syndrome post-parotidectomy. Three hundred and thirty-four patients who underwent a parotidectomy between January 2002 and November 2012 were identified (retrospective study). Of these patients, 102 developed Frey syndrome post-surgery and 232 did not. The time-to-onset analysis enabled us to estimate the risk ratio associated with different types of parotid gland tumours, various parotidectomy procedures, and repeat parotidectomy, which is useful for predicting preoperative and surgical risk. The risk of developing Frey syndrome was lower in patients with malignant tumours than in those with benign tumours (risk ratio 0.351, 95% confidence interval (CI) 0.155–0.594). Risk ratios for lumpectomy PA (pre-auricular area), superficial parotidectomy, and total parotidectomy with respect to lumpectomy T (tail) were 4.378 (95% CI 1.168–16.410), 8.040 (95% CI 3.286–19.670), and 8.174 (95% CI 3.076–21.723), respectively. Repeat parotidectomy also increased the risk of developing Frey syndrome (risk ratio 3.214, 95% CI 1.547–6.678). No effect of the use of a superficial muscular aponeurotic system (SMAS) flap on the risk of developing Frey syndrome was detected (P = 0.888).